Hypersensitivity pneumonitis in fish processing workers diagnosed by inhalation challenge. Issue 4 (3rd October 2018) - Tjalvin, Gro; Svanes, Øistein; Bertelsen, Randi Jacobsen; Hollund, Bjørg Eli; Aasen, Tor B.; Svanes, Cecilie; Kirkeleit, Jorunn
Workers in the fish processing industry have increased risk of developing respiratory diseases due to occupational exposure to bioaerosols and related allergens [1–4]. The literature reports more occupational asthma in workers handling salmon [2, 5], and an exposure–response relationship between total protein exposure and cross-shift changes in forced expiratory volume in 1 s (FEV1 ) and lower respiratory tract symptoms [6]. To our knowledge, there are no published reports on hypersensitivity pneumonitis from this industry. Hypersensitivity pneumonitis is a complex disease for which there are no generally accepted diagnostic criteria, particularly at earlier stages of the disease. We present the case of a fish processing worker diagnosed with hypersensitivity pneumonitis caused by proteins from salmon, in which the aetiology was established using specific inhalation challenge (SIC) as a diagnostic tool. Hypersensitivity pneumonitis may be caused by occupational exposure in the fish processing industry http://ow.ly/GbEf30lFnyk